"Shari'ah compliant hospitality services" or "Muslim friendly hospitality services": searching for a balance - Zawawi, Majdah; Ramli, Noriah (The Malaysian Consumer and Family Economics Association, 2017)
There has been some confusion between the use of the term, Shari'ah compliant hospitality services" and "Muslim friendly hospitality services" amongst practitioners in the Halal tourism industry. This article discusses the core differences and similarities between the two terminologies. It is crucial to resolve any conflicting understanding on the concept in order to ensure that there are no misunderstandings and conceptions when dealing with consumers and the general public. Aside from that, this article also aims at providing a clear picture of how the Shari'ah requirements for Muslim tourists are embedded in the concept of Muslim friendly hospitality services. This is a matter of import for those interested in providing or intending to provide services that cater specifically to the needs of Muslim tourists. This is a conceptual analysis of the Shari'ah legal position as manifested in the Qur'an and Sunnah of the Holy Prophet s.a.w as well as existing legal and administrative framework primarily the MS 2610:2015 Muslim Friendly Hospitality Services Requirements, Malaysia. Concentration is made on the Shari'ah compliant hotels and accommodations in Malaysia, as an example of how these terminologies inter-relate with each other.